Some aspects of management of early pregnacy in women with hypokinesia - Amarachi, Adaeze Uzoma; Elijah, Oluwasegun Ayogbala Adetunji (KhNMU, 2022)
Limiting the volume of muscle activity is an urgent problem in the lives of women around the world. Prolonged hypokinesia affects almost all organs and systems of the human body and is considered stress. The work aimed to study the course of early pregnancy in women with prolonged hypokinesia and to develop tactics for correcting the identified disorders. The essence of the measures was the daily oral use of the drug in tablet form, which included 100 mg of magnesium and 10 mg of pyridoxine. The choice of the drug was since its main action is aimed at reducing the excitability of neurons, as well as neuromuscular transmission, which should be taken into account in the presence of stress for a long time, which is the limitation of the volume of muscle activity. Pyridoxine, which is part of the drug, is involved in metabolic processes that change when exposed to the described factor and, ultimately, cause a violation of the adaptation of the female body to pregnancy.
Keywords: hypokinesia; early pregnancy; stress; pyridoxine